2023
DOI: 10.1038/s41522-023-00438-9
|View full text |Cite
|
Sign up to set email alerts
|

Innovative strategy for the conservation of a millennial mausoleum from biodeterioration through artificial light management

Yuanyuan Bao,
Yan Ma,
Wenjing Liu
et al.

Abstract: Artificial lights can cause critical microbial biodeterioration of heritage monuments by promoting the outbreak of phototrophic microbiomes when they are used for touristic viewing. Here, with the ultimate aim of providing innovative solutions for the conservation and visiting of such monuments, we conducted a pioneering two-year in situ manipulative experiment to evaluate the impacts of different artificial light wavelengths (i.e., blue, green and red lights compared to white light) on the phototrophic microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Similarly, a 2-year-long experiment performed in the Shunling Mausoleum (China) showed that blue light did not affect the biofilms mainly composed of cyanobacteria covering the monument's surfaces at all, while red and, primarily, green rays reduced the biofilms [21].…”
Section: Electromagnetic Radiationmentioning
confidence: 96%
“…Similarly, a 2-year-long experiment performed in the Shunling Mausoleum (China) showed that blue light did not affect the biofilms mainly composed of cyanobacteria covering the monument's surfaces at all, while red and, primarily, green rays reduced the biofilms [21].…”
Section: Electromagnetic Radiationmentioning
confidence: 96%